Microneedling in skin preparation: A narrative literature review (Research, Society and Development, 2025)
Microneedling is a technique that has gained prominence in skin preparation due to its ability to stimulate collagen production and enhance the penetration of topical agents. This procedure involves the use of devices with fine needles that create micro-injuries in the skin, activating the healing process and promoting cell renewal. The aim of this article is to present a narrative review that compiles scientific evidence on microneedling in the treatment of various conditions, such as scars, hyperpigmentation, and skin aging. Additionally, the review explores the safety, indications, and contraindications of the procedure, providing a comprehensive overview of its applications in skin preparation. It is concluded that microneedling, when performed correctly, can be an effective and safe technique, offering significant benefits for skin health and aesthetics.